The U.S. Twin Delivery Volume and Association with Cesarean Delivery Rates: A Hospital-Level Analysis - Easter, Sarah Rae; Robinson, Julian N.; Carusi, Daniela; Little, Sarah E. (American Journal of Perinatology, 2018)
Objective The objective of this study was to test whether hospitals experienced in twin delivery have lower rates of cesarean delivery for twins.Methods We divided obstetric hospitals in the 2011 National Inpatient Sample by quartile of annual twin deliveries and compared twin cesarean delivery rates between hospitals with weighted linear regression. We used Pearson's coefficients to correlate a hospital's twin cesarean delivery rate to its overall cesarean delivery and vaginal birth after cesarean (VBAC) rates.Results Annual twin delivery volume ranged from 1 to 506 across the 547 analyzed hospitals with a median of 10 and mode of 3. Adjusted rates of cesarean delivery were independent of delivery volume with a rate of 75.5 versus 74.8% in the lowest and highest volume hospitals (p = 0.09 across quartiles). A hospital's cesarean delivery rate for twins moderately correlated with the overall cesarean rate (r = 0.52, p < 0.01) and inversely correlated with VBAC rate (r =  − 0.42, p < 0.01).Conclusion Most U.S. obstetrical units perform a low volume of twin deliveries with no decrease in cesarean delivery rates at higher volume hospitals. Twin cesarean delivery rates correlate with other obstetric parameters such as singleton cesarean delivery and VBAC rates suggesting twin cesarean delivery rate is more closely related to a hospital's general obstetric practice than its twin delivery volume.
Keywords: twins; cesarean delivery; vaginal birth after cesarean; vaginal birth; hospital's obstetric culture